Chemical and Sensory Properties of Kefir Produced from Goat milk and Extract Soybean - Nurliyani, Nurliyani; Eni, Harmayani; sunarti, Sunarti; Feny, Prabawati (2014)
Abstract This study was to investigate the effect of combnng goat mlk and extract soybean on the chemcal and sensory qualtes of kefr. Kefr was dvded nto 5 groups, produced from goat and extract soybean mxtures (100:0, 75:25, 50:50, 25:75, 0:100). The chemcal analyss of kefr nclude mosture, fat, proten, ash and carbohydrate content, whereas the sensory propertes nclude aroma, taste, effervescence, sourness, texture and acceptablty. The chemcal data was analyzed by one way ANOVA, whereas the data of sensory propertes was analyzed by non-parametrc Kruskal-Walls method. The total sold of all kefr made from goat mlk and extract soybean mxture was lower (P<0.01) than goat mlk kefr. Carbohydrate of kefr made from goat mlk and extract soybean mxture (75:25, 50:50) was lower (P<0.01) than goat mlk kefr (100:0) or extract soybean kefr (0:100). Whle, the fat content of kefr made from goat mlk and extract soybean mxture (50:50, 25:75) was lower than 100:0 or 75:25. There was no effect of the goat mlk and extract soybean rato n kefr on the proten and ash content.. Extract soybean could affect the aroma and acceptablty, but had no effect on taste, effervescence, sourness and texture of kefr. In concluson, based on chemcal composton, sensory qualty and economc consderaton, the best composte of kefr was obtaned from the rato of goat mlk and extract soybean 50:50. Keywords Chemcal composton, Sensory qualty, Goat mlk, Extract soybean, Kefir